2012
DOI: 10.1074/jbc.m112.365411
|View full text |Cite
|
Sign up to set email alerts
|

Chaperonin Cofactors, Cpn10 and Cpn20, of Green Algae and Plants Function as Hetero-oligomeric Ring Complexes

Abstract: Background:The chloroplast chaperonin system is encoded by multiple genes. Results: The chaperonin cofactors of the green alga C. reinhardtii and the plant A. thaliana form hetero-oligomeric ring complexes containing seven ϳ10-kDa modules. Conclusion:The hetero-oligomeric cofactors were able to interact with chaperonin and assist protein folding. Significance: Formation of hetero-oligomers can explain the occurrence of multiple chaperonin cofactor genes in chloroplasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 60 publications
7
80
1
Order By: Relevance
“…The authors demonstrated that for the singlecelled alga Chlamydomonas (Chlamydomonas reinhardtii), the only functional co-chaperonin form was a mixed oligomer composed of a specific combination of Cpn10 and Cpn20 subtypes. The report showed that this phenomenon was not specific to algae, because Cpn10 and Cpn20 from Arabidopsis were also capable of forming mixed oligomers in vitro, in addition to the previously characterized homooligomers [29]. This finding offered a potential solution to the puzzle of how the homo-oligomeric eight-domained Cpn20, with fourfold symmetry, interacts with the heptameric ring of a Cpn60 oligomer.…”
Section: Box 1 Arabidopsis Chaperonin Familymentioning
confidence: 84%
See 3 more Smart Citations
“…The authors demonstrated that for the singlecelled alga Chlamydomonas (Chlamydomonas reinhardtii), the only functional co-chaperonin form was a mixed oligomer composed of a specific combination of Cpn10 and Cpn20 subtypes. The report showed that this phenomenon was not specific to algae, because Cpn10 and Cpn20 from Arabidopsis were also capable of forming mixed oligomers in vitro, in addition to the previously characterized homooligomers [29]. This finding offered a potential solution to the puzzle of how the homo-oligomeric eight-domained Cpn20, with fourfold symmetry, interacts with the heptameric ring of a Cpn60 oligomer.…”
Section: Box 1 Arabidopsis Chaperonin Familymentioning
confidence: 84%
“…Moreover, in spinach (Spinacia oleracea), specific antibodies to either the Cpn60a or the Cpn60b subunit type were able to coprecipitate both types together [15]. In vitro, Cpn60ab hetero-oligomers have been reconstituted from purified Cpn60a and Cpn60b monomers of pea (Pisum sativum) [19], and a recent study has shown that Arabidopsis (Arabidopsis thaliana) chaperonins expressed in and purified from E. coli form hetero-oligomers composed of seven Cpn60a and seven Cpn60b subunits [29].…”
Section: Composition Of Functional Chloroplast Chaperonin Oligomersmentioning
confidence: 97%
See 2 more Smart Citations
“…The latter gene consists of two linked homologous cpn10 sequences. It is still not completely clear how these subunits oligomerize at the protein level [18], however, it has been reported that the cpn20 subunits may assemble into tetrameric species in vitro [19], or form hetero-oligomers with cpn10 subunits [20]. Until recently, the cpn20 protein was known to exist only in chloroplasts of algae and plants.…”
Section: Introductionmentioning
confidence: 99%